Attenuation coefficient for surface acoustic waves in fluid region - Hang, Bui Thu; Tung, Bui Duc; Dat, Nguyen Tien; Trinh, Chu Duc (Vietnam Journal of Mechanics, 2012)
In recent years, surface acoustic wave devices used in bio-sensing applications have demonstrated high sensitivity in the detection of fluid properties such as density, viscosity, stream velocity. In this paper, a more effective measurement of the SAWsensorstructure is presented. It is reported that at density of 6 g/cm3, the amplitude of mechanical wave is excited while for electrical signal, attenuation at 3 g/cm3 reaches a peak.In our analysis, single–crystal Aluminium Nitride substrate is used. Several parameters of leaky waves including displacement, decay constant in the liquid media are analyzed.